Corporate Social Responsibility Reporting Practices in the Banking Sector of Nepal - Upadhyay-Dhungel, Kshitiz; Dhungel, Amar (Banking Journal, 2013)
Financial institutions not only influence the profit/loss of its shareholders but also drive the economy of the whole nation. So it should be concerned about its social obligation and responsibilities. Social responsibility refers to the obligation of a firm, beyond the required by law of economics, to pursue long-term goals that are good for society. The idea that firms, corporations, and other organizations have social responsibilities leads to the development of the concept labelled as “Corporate Social Responsibility (CSR)” and has evoked widespread interests and concerns both in business and among academicians. Banking sector is under massive pressure from its shareholders, investors, media, as well as its customers to carry out business in a socially responsible and ethical manner. This descriptive study attempts to analyse CSR reporting practices in banking sector of Nepal. For the purpose, ten commercial banks and 4 development banks were selected randomly and their website was scanned to collect data developing a Report Sheet. The total CSR reports were outlined and categorized into different groups. Later on quantitative analysis was also performed and presented using suitable statistical techniques. This study found that CSR is not mandatory in Nepal and all the banks that have made the disclosure of social responsibility have done it in voluntary basis. Among the disclosed information education, training and welfare of underprivileged; arts/heritage and culture protection; contribution to associations, clubs and other organizations; contributions to healthcare and environment; etc were the most commonly reported CSR activities. Child and women developments, religious activity, games and sports activities, blood donations were also among the thrust area for CSR reporting. The disclosures were mostly qualitative with exception of donation and sponsorship amounts. The analysis also shows that most of the Nepalese banks, especially public sector banks, do not mentyion CSR explicitly on their websites. This study strongly recommends the development of uniform standards and framework for reporting of CSR activities, which could be applied to compare it at national levels with other banks and/or industries as well as for the international comparisons. Bank can play a leading role to establish the CSR concepts in Nepalese business and corporations. It is expected that this paper will stimulate more studies in this direction. More such studies should be conducted, especially on developing countries like Nepal, where CSR is at an infant stage of development. In addition to tracing the trend of social disclosure, impacts of social and economic developments on CSR practices, there is also a need to develop a framework for CSR reporting. DOI: http://dx.doi.org/10.3126/bj.v3i1.7511 Banking Journal Vol.3(2) 2013 pp.61-78